Integration of Environmental Ethics Education in the Classroom: A of Related Literature - OLAWUMI, Kayode; MAVUSO, Mzuyanda Percival (PT Keberlanjutan Strategis Indonesia, 2023)
Due to the catastrophic impact of global warming and various environmental challenges, ecological issues are a topic of discussion in every country in the globe. Researchers believed that solutions to environmental problems lie in the integration of environmental ethics education in schools to create awareness of moral values and attitudes of humans toward the environment. However, there seem to be inadequate efforts to integrate environmental ethics education into the school curriculum. This study, therefore, argues for the examined literature to find out how school teachers integrate environmental ethics education in lessons. The study adopted the qualitative systematic literature review method, and twenty-six peer-review articles were selected from the EBSCO, Scopus, and Google Scholar databases. The twenty-six selected peer-review articles were analyzed to determine the level of integration of environmental ethics education in South African classrooms. The study revealed that the internalization of environmental ethics education as a moral foundation may make humans aware of their interaction with the environment. According to literature, awareness of improved environmental ethics education assist human to behave and act ethically towards nature thereby contributing to the reduction in environmental damage and improving environmental conservation and management. The study, therefore, suggests the organization of environmental ethical awareness in-service training programs by the Department of Basic Education for teachers which will expose them and their learners to environmental ethics, disciplined behavior, and positive attitude towards their environment.